A record of Disparalona hamata (Birge, 1879) (Cladocera: Chydoridae) in phytotelmata of Tillandsia aguascalentensis Gardner, 1984 (Poales: Bromeliaceae) - Neretina, Anna N.; Garibian, Petr G.; Romero, Martín; Mondragón, Demetria M.; Silva-Briano, Marcelo (Zootaxa, 2019)
Bromeliads (Bromeliaceae) are an extremely diverse family of the angiosperms widely distributed in the tropical and subtropical regions of the Americas and West Africa. They often serve as phytotelmata, accumulating rainwater between leaves. Such water reservoirs can be inhabited by diverse organisms. But to date not much attention is paid to inventory of these organisms, with careful identification of each taxon. We found a microcrustacean Disparalona hamata (Birge, 1879) (Crustacea: Cladocera) in the bromeliad Tillandsia aguascalentensis Gardner, 1984 in Mexico. Investigated population included parthenogenetic females, gamogenetic females and males. Hereby the population apparently can pass the full life cycle under conditions of phytotelmata. Along with ecological observations, we provide additional taxonomic notes on the genus Disparalona Fryer, 1968 itself. Recently a series of morphological revisions was conducted for this genus. It was subdivided into two subgenera: Disparalona s.str. and Mixopleuroxus Hudec, 2010. But, in fact, the second taxon is a junior synonym of Leptorhynchus Daday, 1905. In this regard here we provide an updated list of taxonomic synonyms for the subgenus Leptorhynchus.